Gaya Kepemimpinan, Motivasi, dan Kepuasan Kerja: Dampaknya terhadap Kinerja Pegawai Dinas Pariwisata Kabupaten Kerinci: Leadership Style, Motivation, and Job Satisfaction: Their Impact on Employee Performance at the Tourism Office of Kerinci Regency - Saputra, Aldi; Yulasmi, Yulasmi; Zefriyenni, Zefriyenni; Zasriati, Masrida (Institut Agama Islam Negeri Kerinci, 2025)
Purpose: This study aims to analyze the role of leadership and motivation in improving employee performance and to examine the role of job satisfaction as a mediating variable. Design/Methodology/Approach: This research employed a quantitative causal approach with data collected through questionnaires. The study involved 50 respondents determined using a saturated sampling method. The analytical technique applied was Structural Equation Modeling (SEM) with a Partial Least Squares (PLS) approach. Findings: The results reveal that leadership style has a positive and significant effect on job satisfaction, and work motivation also has a positive and significant effect on job satisfaction. Furthermore, leadership style significantly and positively influences employee performance, as does work motivation. However, job satisfaction shows a negative and insignificant effect on employee performance. In addition, job satisfaction does not mediate the relationship between leadership style and employee performance, nor between work motivation and employee performance. Research Implications: The findings highlight the importance of effective leadership and strong work motivation in enhancing employee performance in the public sector, particularly at the Kerinci Tourism Office. Nevertheless, job satisfaction does not serve as an effective mediating factor in strengthening these relationships. Therefore, organizations need to design participative leadership strategies and more targeted motivation policies to improve employee productivity.